Instagram Content Analysis of the Women's Empowerment Service, Child Protection and Population Control, Yogyakarta Province on Gender Mainstreaming Issues - Purnamasari, Delima; Edy Susilo, Muhammad (Jurnal Paradigma, 2024)
Yogyakarta is a province with very good gender development when viewed from the Gender Empowerment Index and Gender Development Index. However, gender mainstreaming and performance content produced from the official Instagram @dp3ap2diy is still so minimal that it needs to be examined and analyzed. This research uses descriptive research with a qualitative approach. The data found was analyzed through the process of data collection, data reduction, data presentation, and drawing conclusions. The research results showed that there was 61 content with the theme of gender mainstreaming during the period August 2022-July 2023. The majority of the content, namely 32 uploads were in the form of documentation. The lowest performance was in September with 26 likes, while December was the highest with 1,579 likes. In August, September, January, March, and June no comments were obtained. The message entitled gender mainstreaming shows inconsistencies and there is still content that tends to be masculine or supports excessive burdens on women. Further analysis using the NPower Northwest approach shows that financial aspects can have a broad impact, but there are still shortcomings in conducting research and setting goals. The use of resources is less than optimal and causes organizations to use more reactive communication practices.